Pengaruh Penggunaan Media Pop-Up Book untuk Perkembangan Bahasa Lisan Ekspresif Anak Usia 5-6 Tahun di TK Tunas Harapan Ambarita - Ruth Trya Yogi Manik; Dwi Septi Anjas Wulan (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The aim of this research is to determine the effect of using Pop-up Book Media for the Development of Expressive Spoken Language in children aged 5-6 years. The method used in this research is a quantitative method. This research uses a one-group pretest-posttest design, meaning that the researcher randomly places participants into one group and does not check the condition of other groups to determine stability or clarity before providing treatment. This research was conducted at Tunas Harapan Ambarita Kindergarten, 10 participants were the sample for this research. The null hypothesis of this research was tested using non-parametric statistics. By using the Wilcoxon test, if Tcount is compared with Ttable N 10 with α = 0.05 Ttable = 8. From the data analysis above, it can be said that Tcount > Ttable where 55 > 8, thus the hypothesis is accepted. This means "There is a significant influence of the use of pop-up book media on the development of expressive spoken language in children aged 5-6 years at Tunas Harapan Ambarita Kindergarten.